Nursing care in patients undergoing hematopoietic stem cell transplantation: Scoping review protocol (Research, Society and Development, 2020)
It is a Scoping Review protocol on nursing care in hematopoietic stem cell transplantation. It aims to formalize the primary study. The protocol defines the paths that will be adopted in the secondary Scoping Review study and was elaborated based on the Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocols (PRISMA-P) and the PRISMA Extension for Scoping Reviews (PRISMA -ScR). The review is expected to map the evidence available in the literature on nursing care in HSCT in the hospital environment.